Penerapan Media Pembelajaran Quizizz untuk Meningkatkan Minat Belajar PAI di SMPN 1 Padang Panjang - Rahmi, Raudhatur; Wiza, Rahmi (YASIN, 2025)
This research is motivated by the influence of globalization, characterized by the rapid advancement of science and technology, which presents Indonesia with various challenges and opportunities, particularly in the field of education. The challenges faced by teachers in the learning process are increasing in line with the development of science and technology, where teachers must be able to use engaging, interactive, and enjoyable learning media. One of the interesting and enjoyable media is technology-based media that aligns with the advancements in science and technology, namely Quizizz. The objectives of this study are: first, to determine the application of Quizizz as a learning media in the subject of Islamic Education at SMPN 1 Padang Panjang; second, to assess students' interest in learning through Quizizz in the Islamic Education subject at SMPN 1 Padang Panjang; and third, to identify the supporting and inhibiting factors in using Quizizz as a learning media to enhance students' interest in learning in the Islamic Education subject at SMPN 1 Padang Panjang. The method used in this research is a mixed method with a total of seven informants. The data collection techniques in this study include observation, interviews, questionnaires, and documentation, while the data analysis employs techniques such as data reduction, data presentation, and conclusion drawing or verification. The results of this study indicate that the application of Quizizz in Islamic Education learning has a positive impact on students' interest in learning, as evidenced by positive changes in students' attitudes, where they become more active and enthusiastic during lessons. The implementation of Quizizz as a learning media is carried out in three stages: planning, implementation, and reflection. The use of Quizizz in Islamic Education learning can enhance students' interest in learning, as seen from four indicators of interest: students' feelings of enjoyment, attention, interest, and involvement or participation in the learning process. The main conclusion of this research is that the application of Quizizz can increase students' interest in learning, thereby supporting the achievement of optimal learning objectives. The implications of this research indicate that the integration of technology in the learning process, particularly through the use of interactive media like Quizizz, can significantly enhance students' interest in the subject of Islamic Education. This suggests that teachers need to adopt innovative and engaging teaching methods to create a more dynamic and enjoyable learning environment. Furthermore, this research highlights the importance of training for teachers in utilizing educational technology, enabling them to design and implement effective learning experiences. Thus, the application of technology-based learning media not only contributes to increasing students' interest in learning but also supports the achievement of better educational outcomes in the current era of globalization and technological advancement.